2021
DOI: 10.1097/qco.0000000000000761
|View full text |Cite
|
Sign up to set email alerts
|

Emerging treatment options for cryptosporidiosis

Abstract: Purpose of review Substantial progress has been made recently on the development of new therapeutics for cryptosporidiosis, an infection by the protozoan parasite Cryptosporidium that is associated with diarrhea, malnutrition, growth stunting, cognitive deficits, and oral vaccine failure in children living in low-resource settings. Recent findings Various drug discovery approaches have generated promising lead candidates. The repurposed antimy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Recently, we found that KDU731 is a lead chemical, and has been shown to exhibit substantial in-vitro activity against C. parvum and C. hominis (Love and Choy 2021 ). It is also effective against mouse and calf models of cryptosporidiosis, along with rat toxicity investigation (Manjunatha et al 2017 ).…”
Section: Anti-parasitic Drugs Repurposingmentioning
confidence: 99%
“…Recently, we found that KDU731 is a lead chemical, and has been shown to exhibit substantial in-vitro activity against C. parvum and C. hominis (Love and Choy 2021 ). It is also effective against mouse and calf models of cryptosporidiosis, along with rat toxicity investigation (Manjunatha et al 2017 ).…”
Section: Anti-parasitic Drugs Repurposingmentioning
confidence: 99%
“…It is estimated that Cryptosporidium spp. are responsible for approximately 7.6 million cases and between 48,000 and 202,000 annual deaths among young children in low‐resource environments (Haghi et al., 2020 ; Love & Choy, 2021 ; O'Leary et al., 2021 ). Cryptosporidium has the potential to cause water‐borne epidemics and widespread outbreaks in developing and developed countries (Gururajan et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that Cryptosporidium spp. are responsible for approximately 7.6 million cases and between 48,000 and 202,000 annual deaths among young children in low-resource environments (Haghi et al, 2020;Love & Choy, 2021;O'Leary et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect on parasite growth was variable and did not correlate well with enzyme inhibition ( Kuhlenschmidt et al., 2016 ), conversely as demonstrated by Toxoplasma gondii . It also has shown issue challenges related to cardiovascular toxicity, teratogenicity, and varying efficacy ( Choi et al., 2020 ; Love and Choy, 2021 ). Another series of BKI compounds have been developed which inhibit CDPK.…”
Section: Recent Approaches To Drug Developmentmentioning
confidence: 99%